THE ROLE OF NURSES IN CARING FOR PATIENTS UNDERGOING COLONOSCOPY AT INPATIENT DEPARTMENT - Panatara, Saowapa (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2024)
Currently, the number of patients undergoing inpatient colonoscopies is increasing. The quality of bowel preparation is a crucial factor for successful colonoscopy. Studies indicated that 25% of ineffective colonoscopy results were due to inadequate bowel preparation. This leads to unsuccessful treatment procedures, the need for repeat examinations, delays in diagnosis and treatment, prolonged hospital stays, and increased medical expenses. The purpose of this article is to disseminate the role of nurses in caring for patients undergoing inpatient colonoscopy to ensure effective bowel preparation before the procedure. This role encompasses several aspects, including: physical preparation, which involves assessing the patient's physical and mental condition, reviewing their medication history to identify drugs that should be discontinued (e.g., aspirin, Plavix, warfarin, and herbal medicines), and guiding patients on proper bowel preparation using diet, laxatives, and information about potential complications; monitoring and safeguarding patient rights, which includes ensuring timely intake of laxatives, evaluating the quality of bowel preparation, and addressing issues if the preparation is inadequate; monitoring for risks such as falls and fatigue caused by fluid loss during bowel movements; psychological preparation, which focuses on counseling patients to build confidence, reduce anxiety, and promote cooperation during treatment; and finally, post-procedure care, which involves providing support when patients are transferred to the ward, offering guidance on the recovery, and advising on self-care practices upon discharge.